Promoting Intercultural Competence (IC) through Student’ Exchange Program (EP) in Higher Education in Indonesia - Syam, Sriwidayani; Ansar, Ahlun; Tompong, By Tri Agung Nusantara Kr. J.; Alfatih, Ainun Najib (Indonesian Journal of Educational Studies, 2024)
Globalization has redefined the skills required for success in higher education, with intercultural competence (IC) emerging as a critical attribute for global citizens. This study explores the role of student exchange programs in promoting IC among higher education students in Indonesia, focusing on four key dimensions: cultural awareness, knowledge, attitude, and language skills. Drawing on theoretical frameworks and empirical evidence, this paper examines the transformative potential of exchange programs in enhancing students' ability to navigate diverse cultural contexts. Despite the documented benefits, such as improved cultural sensitivity, broader knowledge horizons, and enhanced employability, challenges remain, including socio-economic constraints and adaptation issues in host countries. By addressing these dynamics within Indonesia’s unique socio-economic and educational landscape, this study provides valuable insights into the internationalization of higher education in emerging economies. The findings underscore the need for comprehensive program design and policy interventions to ensure equitable access and sustained development of IC. This research contributes to the broader discourse on global education and offers practical recommendations for institutions and policymakers to optimize the impact of exchange programs.